2019
DOI: 10.1016/j.quascirev.2019.105875
|View full text |Cite
|
Sign up to set email alerts
|

Chronology and sedimentology of a new 2.9 ka annually laminated record from South Sawtooth Lake, Ellesmere Island in this NOAA depository: https://www.ncdc.noaa.gov/paleo/study/33214

Abstract: Few annually laminated (varved) lacustrine records exist in the Arctic, but these highresolution climate archives are needed to better understand abrupt climate change and the natural mode of climate variability of this sensitive region. This paper presents a new highresolution 2900-year long varved lake sediment record from the Fosheim Peninsula, Ellesmere Island. The varve chronology is based on multiple varve counts made on highresolution scanning electron microscope images of overlapping sediment thin sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…South Sawtooth Lake (hereafter SSL; Fig. 1 A ), located on the Fosheim Peninsula, Ellesmere Island, is an 80-m-deep lake ( 16 , 18 ) which became ice-free between 8,000 and 6,000 y cal B.P. ( 19 ).…”
Section: Study Sitementioning
confidence: 99%
See 4 more Smart Citations
“…South Sawtooth Lake (hereafter SSL; Fig. 1 A ), located on the Fosheim Peninsula, Ellesmere Island, is an 80-m-deep lake ( 16 , 18 ) which became ice-free between 8,000 and 6,000 y cal B.P. ( 19 ).…”
Section: Study Sitementioning
confidence: 99%
“…( 19 ). Previous studies have shown that the sedimentary record contains clastic varves (annual laminations) and that the main sediment fluxes to the lake are primarily driven by snowmelt and occasional summer rainfall events ( 16 , 20 ). The presence of several river channels that converge into one main inlet on the east side of the catchment makes it an ideal lake to study the hydroclimate of this region ( SI Appendix , Fig.…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations